Tracking multidrug resistant tuberculosis: a 30-year analysis of global, regional, and national trends - Hui-Wen Song; Hui-Wen Song; Hui-Wen Song; Jian-Hua Tian; Hui-Ping Song; Si-Jie Guo; Si-Jie Guo; Ye-Hong Lin; Ye-Hong Lin; Jin-Shui Pan; Jin-Shui Pan; Jin-Shui Pan (Frontiers Media S.A., 2024)
ObjectivesTo provide valuable insights for targeted interventions and resource allocation, our analysis delved into the multifaceted burden, trends, risks, and projections of multi drug resistant tuberculosis (MDR-TB).MethodsThis research employed data from the Global Burden of Disease (GBD) 2019 dataset, which used a comparative risk assessment to quantify the disease burden resulting from risk factors. Initially, this database was utilized to extract details concerning the disability-adjusted life years (DALYs), mortality, incidence, and the number of individuals afflicted by MDR-TB. Subsequently, regression analyses were conducted using the Joinpoint program to figure average annual percent change (AAPC) to ascertain the trend. Thirdly, the age-period-cohort model (APCM) was adopted to analyze evolutions in incidence and mortality. Finally, utilizing the Nordpred model within R software, we projected the incidence and mortality of MDR-TB from 2020 to 2030.ResultsMDR-TB remained a pressing global health concern in regions with lower socio-demographic indexes (SDI), where the AAPC in DALYs topped 7% from 1990 to 2019. In 2019, the cumulative DALYs attributed to MDR-TB tallied up to 4.2 million, with India, the Russian Federation, and China bearing the brunt. Notably, the incidence rates have shown a steadfast presence over the past decade, and a troubling forecast predicts an uptick in these areas from 2020 to 2030. Additionally, the risk of contracting MDR-TB grew with advancing age, manifesting most acutely among men aged 40+ in lower SDI regions. Strikingly, alcohol consumption had been identified as a significant contributor, surpassing the impacts of smoking and high fasting plasma glucose, leading to 0.7 million DALYs in 2019.ConclusionsA robust strategy is needed to end tuberculosis (TB) by 2030, especially in lower SDI areas.